2022
DOI: 10.11604/pamj.2022.43.165.37314
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy trends in Ghana: a cross-sectional study exploring the roles of political allegiance, misinformation beliefs, and sociodemographic factors

Abstract: Introduction Africa has the slowest COVID-19 vaccination rate of any continent in the world, with only 29.8% of the population receiving at least one dose of the vaccine. This includes Ghana, where only 37.8% of the country have received at least one dose as of October, 2022. The key aims of this research were to determine levels of hesitancy in COVID-19 vaccines among unvaccinated individuals in Ghana and observe their trends across time, and to identify independent predictors associated with vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…On the other hand, Fu N, et al suggested that the vaccination itself did not influence survival prognoses in patients undergoing pancreatectomy for pancreatic adenocarcinoma (19). Furthermore, in some regions, the COVID-19 vaccine's availability is still limited (20), leading to an increase in the number of cases and potential medical collapse, which could hinder improvement of HPB postoperative mortality rates. Additionally, other factors may still impact HPB postoperative mortality rates despite widespread use of COVID-19 vaccines.…”
Section: Did Covid-19 Vaccinations Improve Outcomes After Hpb Surgery?mentioning
confidence: 99%
“…On the other hand, Fu N, et al suggested that the vaccination itself did not influence survival prognoses in patients undergoing pancreatectomy for pancreatic adenocarcinoma (19). Furthermore, in some regions, the COVID-19 vaccine's availability is still limited (20), leading to an increase in the number of cases and potential medical collapse, which could hinder improvement of HPB postoperative mortality rates. Additionally, other factors may still impact HPB postoperative mortality rates despite widespread use of COVID-19 vaccines.…”
Section: Did Covid-19 Vaccinations Improve Outcomes After Hpb Surgery?mentioning
confidence: 99%
“…Not confident in the safety of the vaccines [7], [26], [30], [44] The significance of demographic analysis is in the provision of valuable information that can inform effective decision-making processes undertaken by governmental bodies and social service organizations [40,41]. Additionally, it aids individuals in comprehending the attributes of a certain population and its potential future transformations, a crucial aspect in informing decision-making processes.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…It is crucial to recognize that demographic factors such as employment status, rural or urban residency, occupation, level of experience, and political party affiliation among opposition voters were not extensively examined in the assessment of factors influencing COVID-19 vaccine acceptance and hesitancy in Ghana (see Figure 4). [5], [8], [11], [13], [27], [34], [37], [49], [44] 9 Gender [6], [8], [11], [30], [35], [37], [42], [44] 8 Religion [8], [13], [15], [27], [34] [42], [44], [49] 8 Age [9], [11], [15], [27], [42], [49] 6 Marital Status [12], [37], [42] 3 Primary source of information about COVID-19 vaccine [11], [13], [44] 3 According to Backhaus [50], urban residency and current pregnancy were significantly and positively associated with refusing vaccination against COVID-19, whereas age, savings, and using contemporary contraceptives were significantly and negatively associated with refusing vaccination. Additional research by Hwang et al [51] indicates that younger age, lack of religious affiliation, political conservatism, and lower family income are also substantially associated with vaccine hesitancy.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on Ghana based on four online cross-sectional surveys conducted in August, 2020 (n = 3048), March, 2021 (n = 1558), June, 2021 (n = 1295), and February, 2022 (n = 424) sought to determine the levels of Covid-19 vaccine hesitancy among unvaccinated individuals [24]. This was motivated by the rationale of Africa's ranking as the continent having the slowest vaccination rate in the world, with Ghana reporting only 27.9% (28.3% as of November 17, 2022) of the country being fully vaccinated and 37.8% receiving at least one dose as of the time of the study [25,26,27].…”
Section: Vaccine Acceptance/hesitancy Factorsmentioning
confidence: 99%